Proposed Marketing Strategy to Increase Brand Awareness of Design Studio in Bandung (Case Study: Quartet Studio, 2019) - Aula, Raisah Fajri (Green Publisher Indonesia, 2025)
In the competitive creative industry, brand awareness plays a crucial role in determining business success. This study addresses the issue of low brand awareness at Quartet Studio, a graphic design studio based in Bandung, despite offering quality services at affordable prices. The objective of this research is to propose a marketing strategy to enhance brand awareness and market penetration. A mixed-method approach was employed, using quantitative questionnaires to assess brand recognition and qualitative analysis of social media and competitor strategies. Analytical tools applied include STP, Marketing Mix, SWOT-TOWS Matrix, Brand Awareness Pyramid, and Porter’s Generic Strategies. The results suggest a marketing strategy focused on the Cimahi and Bandung areas, targeting females aged 17–34. The studio is positioned as an affordable design service with fixed pricing and structured promotions. The findings imply that an integrated digital and offline marketing strategy is essential to strengthen the competitiveness of local creative businesses. This proposed strategy can serve as a reference for other SMEs in similar sectors.